Gardening Without a Garden - Reklis, Kathryn (Cross currents, 2023)
At the intersection of autobiography, critical cultural commentary, and historical mediation, this essay explores the idea of gardening without access to private, self-contained land. It argues that gardening, like language, is the work of the commons - alternatives to histories of enclosure and privatization. Gardens and language are about the commons, about what earth's species have in common with one another and how we choose to entangle our lives in common survival and flourishing.